(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
For the study of the technological solution for the productive management of the banana crop was based on the need of farmers seeking to improve the productive management of the banana crop post-harvest, since using a manual method to record the productive management of the crop are not of great help, due to ignorance of the evolution of technological solutions for the processes of the crop, posed as a general objective to develop a web system through the use of free software tools for monitoring the productive management of the banana crop, the methods used were: descriptive, non- experimental and applicative research, interview and surveys were also used, the same that helped the information gathering that allowed to obtain all the necessary information to establish the requirements in the development of the technological solution, also used the XP methodology the same that allowed to carry an orderly programming that avoided errors in the system, it resulted in a system that has modules such as: Security module, production control module, shipment control module, inventory module, farm control module, advertising and reports. As a conclusion and recommendation, it can be said that the implementation of the web system contributes to improve the management of resources in organizations and increase their productivity, in this case in the banana crop.